Czynniki warunkujące aktywność fizyczną oraz jej oddziaływanie w okresie ciąży = Factors affecting the physical activity and its effect during pregnancy - Agnieszka Gdańska; Marzena Ślężyńska; Danuta Wiśniewska (Kazimierz Wielki University, 2016)
Gdańska Agnieszka, Ślężyńska Marzena, Wiśniewska Danuta. Czynniki warunkujące aktywność fizyczną oraz jej oddziaływanie w okresie ciąży = Factors affecting the physical activity and its effect during pregnancy. Journal of Education, Health and Sport. 2016;6(9):699-711. eISSN 2391-8306. DOI http://dx.doi.org/10.5281/zenodo.159210 http://ojs.ukw.edu.pl/index.php/johs/article/view/3893 https://pbn.nauka.gov.pl/sedno-webapp/works/750420       The journal has had 7 points in Ministry of Science and Higher Education parametric evaluation. Part B item 755 (23.12.2015). 755 Journal of Education, Health and Sport eISSN 2391-8306 7 © The Author (s) 2016; This article is published with open access at Licensee Open Journal Systems of Kazimierz Wielki University in Bydgoszcz, Poland Open Access. This article is distributed under the terms of the Creative Commons Attribution Noncommercial License which permits any noncommercial use, distribution, and reproduction in any medium, provided the original author(s) and source are credited. This is an open access article licensed under the terms of the Creative Commons Attribution Non Commercial License (http://creativecommons.org/licenses/by-nc/4.0/) which permits unrestricted, non commercial use, distribution and reproduction in any medium, provided the work is properly cited. This is an open access article licensed under the terms of the Creative Commons Attribution Non Commercial License (http://creativecommons.org/licenses/by-nc/4.0/) which permits unrestricted, non commercial use, distribution and reproduction in any medium, provided the work is properly cited. The authors declare that there is no conflict of interests regarding the publication of this paper. Received: 02.09.2016. Revised 24.09.2016. Accepted: 24.09.2016.       Czynniki warunkujące aktywność fizyczną oraz jej oddziaływanie w okresie ciąży   Factors affecting the physical activity and its effect during pregnancy   Agnieszka Gdańska Akademia Wychowania Fizycznego im. Jerzego Kukuczki w Katowicach Katedra Nauk Fizjologiczno-Medycznych, Zakład Biochemii   Marzena Ślężyńska Akademia Wychowania Fizycznego im. Jerzego Kukuczki w Katowicach Zakład Rekreacji Fizycznej, Katedra Rekreacji   Danuta Wiśniewska Akademia Wychowania Fizycznego im. Jerzego Kukuczki w Katowicach Katedra Teorii i Metodyki Wychowania Fizycznego, Zakład Korekcji Wad Postawy     Streszczenie   Aktywność fizyczna w czasie trwania ciąży korzystnie wpływa na poprawę wydolności układu krążenia, funkcje układu mięśniowo-szkieletowego, układu trawiennego oraz procesów metabolicznych [8]. Ćwiczenia fizyczne mogą powodować krótko i długotrwałe korzyści dla matki i rozwijającego się płodu. Dlatego aktualne trendy w opiece nad kobietami ciężarnymi polegają na propagowaniu aktywności fizycznej w różnym stopniu przez cały okres ciąży [10]. Cel badań. Celem badań była analiza czynników, które warunkowały na ograniczenie, rozpoczęcie lub kontynuowanie wysiłku fizycznego w czasie ciąży. Jednocześnie porównywano oddziaływanie aktywności fizycznej na przebieg ciąży, porodu oraz ogólny stan zdrowia i samopoczucia. Materiał i metody badań. Badaniami objętych zostało 50 kobiet w wieku 15-55 lat mieszkających w powiecie Wodzisław Śląski. W badaniach wykorzystano autorski kwestionariusz. Wszystkie kobiety uczestniczące w badaniach były matkami i przebyły poród. Wyniki badań. Wśród 50 ankietowanych dominowały kobiety w przedziale wieku 20-29 lat. Większość badanych (68%) deklarowała, że wykonywały ćwiczenia fizyczne w czasie ciąży, ale zaledwie 16 kobiet (32%) oświadczyło, że ciąża wyzwoliła motywację do aktywności fizycznej. Co trzecia kobieta (32%) deklarowała, że niezależnie od trymestru na aktywność fizyczną w trakcie ciąży przeznaczała tygodniowo 1-2 godz. Podobnie niemal co trzecia respondentka (30%) wyrażała opinię o korzystnym oddziaływaniu ruchu w trakcie ciąży na poród. Wnioski. Aktywność fizyczna w czasie ciąży pozwalała zachować prawidłową masę ciała, poprawiała nastrój psychiczny oraz skuteczne przeciwdziałała dolegliwościom związanym z ciążą. W związku z powyższym powinno się propagować aktywność fizyczną w okresie ciąży, szczególnie jeżeli nie ma przeciwwskazań lekarskich. Słowa kluczowe: aktywność fizyczna, ciąża, rekreacja, poród, ból, samopoczucie   Abstract Physical activity during pregnancy is useful for improving cardiovascular efficiency, musculoskeletal system, digestive system and metabolic processes [8]. Exercise can bring short and long-term benefits for women and the developing fetus, therefore, the current trends in the care of pregnant women seek to promote physical activity throughout pregnancy [10]. Aim of the study The aim of the study was to analyze the factors that affect the limitation, of exercise during pregnancy. Comparing the impact of physical activity on pregnancy, childbirth, and overall health and well-being. Material and methods The study included 50 women age 15-55 years living in the district Wodzislaw Slaski. The study has been carried out with the use of the authorial questionnaire-survey. All women participating in the study were mothers and gone through childbirth. Results Among the 50 surveyed dominated women between 20-29. The majority of respondents (68%) declared that they performed physical exercise during pregnancy, but only 32% women stated that the pregnancy triggered motivation for physical activity. Every third woman (32%) declared that regardless of trimester they were exercise during pregnancy and devoted to that activity 1-2 hours per week. 30% of respondents declared positive impact of physical activity during pregnancy to childbirth. Conclusions Physical activity during pregnancy allow to maintain normal weight, improved mood, mental and effectively counteract the discomfort associated with pregnancy. Therefore physical activity should be more popularized during pregnancy especially if there is no medical contraindications. Keywords: physical activity, pregnancy, recreation, childbirth, pain, mood